The Status of Physical Education in Jordanian Basic Stage (Grades 1-3) Schools as Reported by Classroom Teachers - Abu dalbouh, Mousa; Kanan, Eid (Jordan Journal of Educational Sciences, 2005)
This study investigated the status of Physical Education in the Basic Stage schools (grades 1-3) in the Northern part of Jordan. The sample of the study consisted of 230 classroom teachers. For the purposes of this study a sixtytwo- item questionnaire of 4 likert items was developed. Descriptive statistics (frequency and percentages) were used to analyze the collected data. The results revealed that 34.5% of the basic stage classroom teachers were not familiar with the importance of the implementation of physical education activities. The results also revealed that physical education has a low status regarding its suitability to Basic Stage schools. The study recommended conducting in-service workshops for Basic Stage classroom teachers on how to implement new ideas and methods of implementing physical education classes